2021
DOI: 10.1094/pdis-12-20-2652-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Leaf Spot Caused by Diaporthe tulliensis on Boston Ivy (Parthenocissus tricuspidata) in Taiwan

Abstract: Starting from the May to August 2020 (average humidity 76.6% and temperature 25.2°C in Taipei), Boston ivy (Parthenocissus tricuspidata) plants on the campus of National Taiwan University (25°01'05.4"N 121°32'36.6"E) exhibited leaf rusts caused by Phakopsora ampelopsidis (Tzean et al., 2019) and leaf spots caused by an unknown pathogen. The leaf spots appeared reddish to brown color and mostly irregular to round shape on the simple and trifoliate leaflets (Supplemental Figure 1A-C). The leaf spots were surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…D. tulliensis has been recognized as an important pathogen of various hosts, such as kiwifruit [ 47 ], coffee [ 48 ], and grapes [ 13 ]. Interestingly, Huang et al [ 49 ] and Chen and Kirschner [ 50 ] recently reported the same species as a pathogen causing leaf spot on Parthenocissus tricuspidata as well as an endophyte from Nelumbo nucifera in Taiwan, respectively. However, in the present study, none of the strains recognized as D. passiflorae, D. perseae , D. tulliensis , or the new species D. hsinchuensis , satisfied Koch’s postulates after 14 days of incubation.…”
Section: Discussionmentioning
confidence: 99%
“…D. tulliensis has been recognized as an important pathogen of various hosts, such as kiwifruit [ 47 ], coffee [ 48 ], and grapes [ 13 ]. Interestingly, Huang et al [ 49 ] and Chen and Kirschner [ 50 ] recently reported the same species as a pathogen causing leaf spot on Parthenocissus tricuspidata as well as an endophyte from Nelumbo nucifera in Taiwan, respectively. However, in the present study, none of the strains recognized as D. passiflorae, D. perseae , D. tulliensis , or the new species D. hsinchuensis , satisfied Koch’s postulates after 14 days of incubation.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first report of D. tulliensis as a fungal pathogen of betel leaves. Diaporthe tulliensis has been reported to cause leaf spots on coffee in China (Gorg et al ., 2020) and on Parthenocissus tricuspidata in Taiwan (Huang et al., 2021), cacao pod rot in Puerto Rico (Serrato‐Diaz et al ., 2022), and stem canker of kiwifruit in China (Bai et al ., 2017) and of jasmine in Taiwan (Hsu et al., 2023).…”
Section: Figurementioning
confidence: 99%
“…Parthenocissus tricuspidata in Taiwan (Huang et al, 2021), cacao pod rot in Puerto Rico (Serrato-Diaz et al, 2022), and stem canker of kiwifruit in China (Bai et al, 2017) and of jasmine in Taiwan (Hsu et al, 2023).…”
Section: And Onmentioning
confidence: 99%